2022
DOI: 10.3928/19404921-20220218-02
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults' Perceived Risk Regarding COVID-19 and Intention to Vaccinate: Role of Health-Related Literacy

Abstract: The current cross-sectional descriptive study aimed to explore the association between coronavirus disease 2019 (COVID-19)–related health literacy, perceived risk, and intention to receive a COVID-19 vaccine. A sample of 414 older adults completed several questionnaires regarding COVID-19 risk perception, intention to vaccinate, and health literacy. Results revealed that more than one half of older adults demonstrated perceived high risk related to COVID-19 infection. Moreover, 31.6% of older adults noted thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…An overview cross-sectional study done among African countries and middle East countries to ascertain the acceptances, attitude, and belief relating to vaccines in general and the COVID-19 vaccine revealed that 666.81% of respondent would like to be vaccinated against COVID-19, while 33.19% refuse vaccination. Reasons for vaccine hesitancy includes: concerns regarding vaccine side effects, fear of getting sick from uptake of the vaccine, religious belief, and absence of accurate vaccine promotion news [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…An overview cross-sectional study done among African countries and middle East countries to ascertain the acceptances, attitude, and belief relating to vaccines in general and the COVID-19 vaccine revealed that 666.81% of respondent would like to be vaccinated against COVID-19, while 33.19% refuse vaccination. Reasons for vaccine hesitancy includes: concerns regarding vaccine side effects, fear of getting sick from uptake of the vaccine, religious belief, and absence of accurate vaccine promotion news [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a larger effect of warning labels on the perceived healthfulness ratings of a sugary drink was observed among older adults than younger adults from the UK (34) . It has been stated that older adults have greater health risk perceptions (how individuals subjectively estimate and feel about the risks they face) compared with their younger counterparts (35,36) . Others have suggested that older age is associated with an increased tendency to use nutrition labels because of an increased interest in healthy eating as individuals get older (37) and/or increased efforts to meet specific dietary requirements as the metabolism declines with age (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 3 Awareness and use of disclaimer-type labels among Mexican adults and youth they face) compared with their younger counterparts (35,36) . Others have suggested that older age is associated with an increased tendency to use nutrition labels because of an increased interest in healthy eating as individuals get older (37) and/or increased efforts to meet specific dietary requirements as the metabolism declines with age (38) .…”
Section: Adults Youthmentioning
confidence: 99%